2011
DOI: 10.1124/jpet.111.181370
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Endocannabinoid Hydrolytic Enzymes Attenuates Precipitated Opioid Withdrawal Symptoms in Mice

Abstract: ⌬9 -Tetrahydrocannbinol (THC), the primary active constituent of Cannabis sativa, has long been known to reduce opioid withdrawal symptoms. Although THC produces most of its pharmacological actions through the activation of CB 1 and CB 2 cannabinoid receptors, the role these receptors play in reducing the variety of opioid withdrawal symptoms remains unknown. The endogenous cannabinoids, N-arachidonoylethanolamine (anandamide; AEA) and 2-arachidonylglycerol (2-AG), activate both cannabinoid receptors but are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 41 publications
(61 reference statements)
8
83
1
Order By: Relevance
“…Moreover, when it was administered repeatedly to mice, this MAG lipase inhibitor was found to produce physical dependence, as indicated by SR141716A-precipitated paw fluttering, and to cause tolerance to develop both to its own antinociceptive effect, unless it was administered at a low antinociceptive dose, and to that of the direct CB 1 /CB 2 receptor agonists, Δ 9 -tetrahydrocannabinol and R-(+)-WIN55212 (56,73) . In line with some of these observations is the finding that both JZL184 and the direct CB 1 /CB 2 receptor partial agonist, Δ 9 -tetrahydrocannabinol, could reduce four naloxone precipitated physical withdrawal signs in morphine-dependent mice (41) . In contrast, only two of these withdrawal signs could be attenuated by the FAAH inhibitor, PF3845.…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 69%
“…Moreover, when it was administered repeatedly to mice, this MAG lipase inhibitor was found to produce physical dependence, as indicated by SR141716A-precipitated paw fluttering, and to cause tolerance to develop both to its own antinociceptive effect, unless it was administered at a low antinociceptive dose, and to that of the direct CB 1 /CB 2 receptor agonists, Δ 9 -tetrahydrocannabinol and R-(+)-WIN55212 (56,73) . In line with some of these observations is the finding that both JZL184 and the direct CB 1 /CB 2 receptor partial agonist, Δ 9 -tetrahydrocannabinol, could reduce four naloxone precipitated physical withdrawal signs in morphine-dependent mice (41) . In contrast, only two of these withdrawal signs could be attenuated by the FAAH inhibitor, PF3845.…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 69%
“…Spinal cords and brains were rapidly harvested, snap-frozen in dry ice, and stored at 280°C until the time of processing. Tissues were further processed according to methods described previously (Ramesh et al, 2011;Ignatowska-Jankowska et al, 2014). See the (Supplemental Material for details.…”
Section: Methodsmentioning
confidence: 99%
“…Opioid Withdrawal. THC is known to reduce the severity of opioid withdrawal in humans and rodents, and recently endocannabinoid hydrolase inhibitors were also found to alleviate symptoms of precipitated and spontaneous withdrawal in opioid-dependent mice (Ramesh et al, 2011). Treatment of morphinedependent mice with the mu opioid receptor antagonist nalaxone induces a profound withdrawal phenotype consisting of jumping, paw tremors, diarrhea, and weight loss.…”
Section: E Addiction and Withdrawalmentioning
confidence: 99%
“…However, several studies have reported that lower doses of JZL184 that partially inhibit brain MAGL and cause submaximal elevations in brain 2-AG (Long et al, 2009b) retain efficacy in rodent models of pain (Busquets-Garcia et al, 2011;Ghosh et al, 2012), anxiety (Busquets-Garcia et al, 2011;Kinsey et al, 2011;Sciolino et al, 2011), emesis (Sticht et al, 2011), and opioid withdrawal (Ramesh et al, 2011). Importantly, the antinociceptive and anxiolytic-like effects elicited by a low dose of JZL184 (8 mg/kg i.p.)…”
mentioning
confidence: 99%